Tetraspanin TSP-12 and SUP-17/ADAM10 exhibit cell type–specific codependence for trafficking through the Golgi - Zhiyu Liu; Byron Williams; Lin Wang; Frances K. Clark; Ryan C. Vignogna; J. Christopher Fromme; Jun Liu (Proceedings of the National Academy of Sciences, 2026)
A subset of the four-pass transmembrane proteins called C8 tetraspanins (TspanC8) can bind and promote the cell surface localization of ADAM10 (A Disintegrin and Metalloproteinase 10). ADAM10 is a conserved transmembrane metalloprotease essential for metazoan embryonic development and human health. However, the in vivo functional relationships between C8 tetraspanins and ADAM10 are not fully understood. Caenorhabditis elegans has two paralogous tetraspanins, TSP-12 and TSP-14, that resemble the mammalian TspanC8 proteins. We have previously shown that TSP-12/TspanC8 can bind SUP-17/ADAM10 and promote its cell surface localization in early embryos. In this study, we identified the specific step in the secretory pathway where TSP-12–SUP-17 interaction is needed. We found that TSP-12 and SUP-17 share a mutually dependent, yet cell type– and developmental stage–specific relationship in their Golgi trafficking itinerary. In the early embryo, TSP-12 and SUP-17 depend on each other for their transit through the Golgi. However, only SUP-17 is required for proper Golgi trafficking of TSP-12 in the developing oocytes. We further showed that the ER accumulation of SUP-17 in embryos lacking TSP-12 is mediated by the Retention in Endoplasmic Reticulum 1 protein RER-1. These findings, combined with our previous work showing that TSP-12 and TSP-14 function redundantly in endosomes for the recycling of the type II receptor of the BMP signaling pathway, showcase the dynamic and versatile functions of TSP-12 in membrane trafficking in specific cellular contexts. They further highlight the importance of dissecting the functional relationships between TspanC8 proteins and ADAM10 in vivo.